PENGEMBANGAN GERAKAN GO GREEN DI SEKOLAH DALAM MENINGKATKAN NASIONALISME (Studi Di SMP Negeri 2 Dawuan Kabupaten Subang) - Ridwan Lesmana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
Environmental problem sarieas a result of human activity itself, from time to time a threat to Increasing environmental damage. Society has not shown aware nessin maintaining and managing the real environment.Many various illegal logging, exploitation of natural resources, littering, waste management out of control, are the kinds of actions that pollute and damage the environment. Looking at this, it is important and urgent agenda to do is build a culture of Go Green in every spheres of life. Forthat purpose, the schoolas an educational institution, can bein seminated and rooting media values- based culture of clean living environment that is useful for individuasl and public life learners. Schools must develop order and social-pedagogical culture that is conducive to the growth of a variety of personal qualities loving environment. The findings of this study are: (1) the behavior of learners in the development of the Go Green movement can boost nationalism, (2) the existence of barriers and obstacles in the development and implementation of the Go Green at the school, (3) Go Green movement prospects to the school, community and environment. The study recommends to stakeholders SMPN 2 Dawuan Subang to reinforce the perception of the Go Green movement, and the creation of school cultures that manifest Go Green environmentally friendly school with discipline frame so that learner sincreased nationalism.